The Impact of CdS Nanoparticles on Ploidy and DNA Damage of Rucola (Eruca sativa Mill.) Plants. (24th December 2015) - Kokina, Inese; Jahundoviča, Inese; Mickeviča, Ilona; Sledevskis, Eriks; Ogurcovs, Andrejs; Polyakov, Boris; Jermaļonoka, Marija; Strautiņš, Jānis; Gerbreders, Vjaceslavs
Abstract : The genotoxic effect of cadmium sulfide nanoparticles (CdS NPs) of different sizes in rucola ( Eruca sativa Mill.) plants was assessed. It was confirmed that nanoparticles < 5 nm in size were more toxic than larger particles at an identical mass concentration. Significant differences in cell ploidy, as well as in the mitotic index, were detected between control and treated samples. Differences in the DNA banding pattern between control samples and samples after treatment with cadmium sulfide nanoparticles were significant and detected at different places as the appearance or elimination of DNA fragments. Fluorescence images showed that cadmium sulfide nanoparticles smaller than 5 nm in size can diffuse through the membrane and their presence affects the genetic system of the plant.